Flood Syndrome as a Complication of Umbilical Hernia in a Cirrhotic Patient: Surgical Timing Consideration - Zepeda, Brayan Alonso Flores; Zavala, Pedro Alejandro Magaña; Valle, José Emaús Soto; López, Vicente Nieto (British Journal of Healthcare and Medical Research, 2025)
Introduction: The incidence of umbilical hernia (UH) in cirrhotic patients with ascites is approximately 20%, which is ten times higher than in the general population, and can reach up to 40% in cases of large-volume ascites. These patients often present with systemic complications associated with cirrhosis, significantly increasing their risk of infections and necessitating close monitoring. Although uncommon, rupture of an umbilical hernia represents a serious and potentially life-threatening complication in patients with massive ascites and advanced liver disease. This event leads to spontaneous leakage of ascitic fluid, known as Flood syndrome. This condition poses a considerable clinical challenge due to the lack of clear guidelines for its management and ongoing controversy regarding the optimal therapeutic approach.